PERBUATAN MELAWAN HUKUM TERHADAP IZIN USAHA PERTAMBANGAN BATUBARA (Studi Putusan No.10Pdt.G2015PN. Tgt) - Muhammad Afdal Nazir; Elfrida Ratnawati (UNES Law Review, 2023)
The coal commodity mining industry in Indonesia has various kinds of legal problems in its management, including regarding overlapping coal Mining Business Permits (IUP), because in the same IUP Area coal IUP has been issued by the relevant government to two different parties, causing disputes between the parties holding the IUP that are protracted and tend to be no legal certainty for IUP holders to be able to carry out its business activities as experienced by PT Pasir Prima Coal Indonesia (PT. PPCI) as the holder of the Production Operation IUP, which in its IUP Area has been issued another IUP on behalf of PT Mandiri Sejahtera Energindo (PT. MSE), thus causing a dispute between the two parties, why did this happen, is there any unlawful act on it? For this reason, it needs to be legally tested through the Court in order to achieve legal certainty regarding who is more entitled to carry out mining activities in the IUP Area. After there is legal certainty with a court decision with permanent legal force (Inkracht van gewijsde), then what about IUP to carry out mining activities within the IUP Area after Decision No.10 / Pdt.G / 2015 / PN.Tgt.? Therefore, the author is interested in analyzing Decision No.10/Pdt.G/2015/PN.Tgt using qualitative normative research methods, while the results found that the IUP holders of PT. PPCI, which has also been decided by the Tanah Grogot District Court (Inkracht van gewijsde) as the party entitled to the disputed IUP Area, has not been able to carry out mining activities in the IUP area, which on the contrary is PT. MSE that has carried out mining activities in the IUP area, or in other words, legal certainty has not been achieved for PT. PPCI.